Organizational happiness: mediation between employee valuation and productivity. A look at its management in the state sector (2019)
This paper addresses the issue of organizational happiness and its impact on the employee-productivity relationship. The goal of the research was to diagnose the state of the perception of organizational happiness of the administrative personnel of a public higher education institution Department of Córdoba (Colombia), relying on four dimensions: Teamwork, satisfaction, commitment, and innovation. Through a qualitative-quantitative and exploratory research, a representative and random sample comprised by 297 administrative employees assigned to three offices located in the municipalities of Montería, Lorica and Berástegui, with a margin of error of 0.03%, was analyzed. The findings show the potential of the teamwork and commitment dimensions to the organization / function, and the need to strengthen job satisfaction and innovation as determining factors in individual expectations and experiences, interpersonal relationships, motivation, adaptability, diversity of methods, work well-being, and appropriation. It is concluded that the university –distinguished by being traditional and influential, with a complex structure, a number of employees that exceeds six hundred people, and subject to surveillance by the State– has made efforts in matters of work climate, but lacks institutional policies that measure organizational happiness as the gear for business development based on employee assessment and productivity.